Does recession reduce global health aid? Evidence from 15 high-income countries, 1975–2007 - Stuckler, David (World Health Organization, 2011)
OBJECTIVE: To test the hypothesis that economic recessions lead to reduced global development assistance for health (DAH). METHODS: Data obtained from the Creditor Reporting System of the Organisation for Economic Co-operation and Development (OECD) for 15 OECD countries were used to model the percentage change (relative difference) in commitments and disbursements for DAH as a function of three measures of economic recession: recessionary year (as a dummy variable with 0 for no recession and 1 for recession), percentage change in per capita gross domestic product and percentage point change in unemployment rate for recessionary cycles from 1975 through 2007. We looked for an association both during the concurrent recessionary year and one and two years later. FINDINGS: No statistically significant association was found in the short or long run between measures of economic recession and the amount of official DAH committed or disbursed. CONCLUSION: Any important decrease in overall DAH following the current economic recession would have little historical precedent and claims of inevitability would be unjustifiable.